The health system in Argentina: an unequal struggle between equity and the market (Italian Journal of Public Health, 2012)
The modern health system of Argentina was developed in 1945-1955, a period of economic bonanzacharacterized by industrialization, rapid urbanization and activist labor organizations. During the ensuingyears it evolved in three sectors: public, social security and private, with separate services, populationcoverage and funding. While the national Ministry of Health is nominally responsible for general healthpolicies and regulations, overseeing the general operation of health services, designing preventive medicineprograms and negotiating the coverage and fees of health insurance plans, it has in fact very low leverage toenforce decisions in the provinces, which are autonomous, as well as in the social security and private sectors,which are weakly regulated if at all. While the health workforce, medical facilities and level of spending areacceptable, the fragmentation and segmentation of the system render it highly inequitable and inefficient.During the 1980s and 1990s, the health system has experienced further transformations, as neoliberalpolicies took hold in the country and dictated a reduction of state involvement in social services in favor ofprivatization and decentralization of health care. The result has been increased fragmentation, inequity andinefficacy, as health care is increasingly prey to the economic interests of private corporations (insuranceand pharmaceutical industries), trade union bureaucracies and the medical professional and technologyestablishments. The expectation of popular sectors of society are that progressive polices recently enactedby Congress, and being implemented in the fields of education, retirement pensions and the media, will befollowed with much needed public health policies based on equity and efficiency.
Keywords: Argentina; public health; health system; health services; equity